Winda Sari, Yuzaidi PEMIKIRAN HADIS JOSEPH SCHACHT DAN BANTAHAN TERHADAPNYA - Winda Sari (Al-Mu'tabar, 2022)
Hadith as the second source of law in Islam plays an important role for Muslims. However, the existence and authenticity of the hadith still received negative comments from several parties, including the orientalists. Orientalist who is famous for his analysis of the Prophet's Hadith is Joseph Schacht. This paper aims to identify Joseph Schacht's opinions about the hadith and rebuttal to Joseph Schacht's opinion by using the literature study method. The results show that there are several figures who dispute Joseph Schacht's opinion on Hadith such as M.M. A'zami. Rebuttal from M.M. A'zami scientifically proves that Joseph Schacht's opinion about Hadith is not true. Some further research is expected to enrich the scientific treasures, especially in the field of Hadith.